Response of ground macrolichens to site factors, co‐existing plants and forestry in boreal forests - Tonteri, Tiina; Hallikainen, Ville; Merilä, Päivi; Miina, Jari; Rautio, Pasi; Salemaa, Maija; Tolvanen, Anne
Aim Ground lichens have declined in boreal and temperate Europe. The potential causes of the decline were explored by analysing the response of lichen cover to forest management, site and stand variables as well as co-existing plants in different boreal vegetation subzones. Location Finland. Methods Understorey vegetation was surveyed on a systematic network of 1721 sample plots in forests on mineral soil. The response of macrolichen cover to explanatory variables was analysed by generalised linear mixed models (GLMMs). Results Ground lichens favoured old Pinus sylvestris forests on xeric sites with sufficient light conditions. Intensive forest management regimes, such as regeneration cutting and soil ploughing decreased lichen cover, while lighter scarification methods had less effect on lichens. Lichens benefitted from intermediate cutting on sites with low bryophyte cover. Lichens responded similarly to site and stand variables in all boreal subzones, showing that despite heavy reindeer grazing these response patterns apply also in the northern boreal subzone. Lichens showed both negative (Vaccinium myrtillus, Empetrum nigrum and Calluna vulgaris) and positive (Vaccinium vitis-idaea) responses to increasing dwarf shrub cover. Generally, lichens negatively responded to increasing bryophyte cover, indicating either that bryophytes benefit from a decline of lichens or that there is real competition between these groups. The negative relationship between bryophytes and lichens strengthened as the tree canopy becomes denser. Conclusions Our study provides new quantitative insights into the effects of forest management and changes in forest structure as underlying factors for lichen decline both inside and outside the reindeer-herding area (i.e., the northern boreal subzone). These factors include increased canopy cover with increased shading as well as disturbance caused by regeneration cutting and soil preparation. The possible effects of the long-term legacy of nitrogen deposition, lack of forest fires and ...